2013
DOI: 10.22401/jnus.16.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Compression and Dielectric strength properties for Epoxy/Polyurethane Blends reinforced with glass fibers

Abstract: Compression and dielectric strength properties of EP/PU blends composites reinforced with two layers of random direction glass fibers have been investigated. Hand lay up method was used to prepare sheets of EP/PU blends composites with different weight percentage of PU(12.5%,25% and37.5%). Results show that the compression value increase with the increasing of the weight percentage of PU in the blended matrix composite and became higher than for epoxy composite, while the results of the dielectric strength sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Different concentrations of polyurethane were used (0%, 12.5%, 25%, 37.5% and 100%). The study showed that compressive strength increased and electrical insulation resistance decreased with increasing polyurethane ratios [6]. The present work aims to study the effect of temperature and natural filler volume fraction on the mechanical (impact strength and hardness) and physical properties (thermal conductivity) of a binary polymeric mixture consisting of epoxy resin with polyurethane.…”
Section: Introductionmentioning
confidence: 98%
“…Different concentrations of polyurethane were used (0%, 12.5%, 25%, 37.5% and 100%). The study showed that compressive strength increased and electrical insulation resistance decreased with increasing polyurethane ratios [6]. The present work aims to study the effect of temperature and natural filler volume fraction on the mechanical (impact strength and hardness) and physical properties (thermal conductivity) of a binary polymeric mixture consisting of epoxy resin with polyurethane.…”
Section: Introductionmentioning
confidence: 98%
“…This leads to an increase in compressive stress required for deforming the composite. In contrast to tensile load, where fibers in the direction of applying force have the most significant effect on increasing strength, fibers perpendicular to the direction of applied force have the most significant impact on increasing strength in compression [36].…”
Section: Figure 12mentioning
confidence: 87%
“…The combination of the high capability of rubber to deform in a non-destructive mode with the increased rigidity of epoxy generated by the highly cross-linked structure, especially when epoxy is blended with polyurethane, boosts the compressive strength to a higher level than pure epoxy [44].…”
Section: Compressive Strengthmentioning
confidence: 99%